Topological Shape Optimization of Permanent Magnet in Voice Coil Motor Using Level Set Method - Lee, Jangwon; Wang, Semyung (IEEE transactions on magnetics, 2012)
In this paper, a voice coil motor is optimized using the single-phase and the multi-phase level set method, and the magnetic saturation effect is considered in the optimization. The normal velocities on the moving boundaries are calculated by a design sensitivity analysis (DSA) using the adjoint variable method (AVM). In the first numerical example using a C-core actuator, the level set based optimization is compared with conventional topology optimization. In the second numerical example of the voice coil motor, optimizations using the single-phase and the multi-phase level set method are performed to maximize the Lorentz force on the moving coil by means of the optimal shapes of the permanent magnet and the ferromagnetic material in a design domain.